On quotients of the Riemann zeta function at consecutive positive integers - Kohnen, Winfried (Proceedings of the American Mathematical Society, 2022)
We express the quotients of the Riemann zeta function at consecutive positive integers in terms of the limit of an average sum of quotients of special values of Dirichlet L-functions.